The Role of Religiosity and Scriptural Interpretation on Ambivalent Sexist Attitude - Sağnıç, Hasan Adar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The current study was initiated on the basis of previous research providing contradictory findings with regards to the relationship between religiosity and ambivalent sexism in the literature. The current study was the first experimental research on the related topic, hypothesizing that manipulation of Qur’anic verses’ interpretation (simply, by providing different interpretations of verses translated and interpreted by scholars with distinct perspectives) would influence participants’ sexism related attitudes. For that purpose, participants were allocated to three different conditions and each group was provided with a distinctive interpretation of a Qur’anic verse. The control group received an egalitarian inducing version [33:35] whereas the benevolent and hostile sexism inducing groups received different interpretations of the same verse [4:34]. It was expected that ambivalent sexism scores would vary based on what was induced. Also, parental religiosity (mother and father), participants’ religiosity and scriptural literalism were included as control variables. Findings revealed the effectiveness of the interpretation provided for the control group. Additionally, men scored higher than women for all conditions and hostile sexism for men was induced successfully however none of the sexism types were induced in women. The findings of the study are discussed in light of the literature. Keywords: Ambivalent sexism, Islam, Religiosity, Qur’anic interpretation.

ÖZ: Bu çalışma, literatürde bulunan çelişkili cinsiyetçilik ve dindarlık arasındaki ilişkiyi inceleyen araştırmaları temel alarak başlatılmıştır. Geçmiş çalışmalardan elde edilen önerilerden yola çıkılarak, bu çalışmanın amacı belirlenmiştir. Bu çalışma konuyla ilgili ilk deneysel araştırma olup Kur’an ayetlerinin meallerinin manipüle edilmesinin (basitçe, farklı görüşteki çalışmacılar tarafından çevrilen ve yorumlanan ayetlerin sunulması) katılımcıların cinsiyet ayrımına dair tutumlarını etkileyebileceği hipotezi öne sürülmüştür. Bu amaçla, katılımcılar üç farklı koşula ayrılmış ve her gruba Kur’an ayetlerinin farklı bir meali (yorumlaması) sunulmuştur. Kontrol grubuna eşitlikçi tutum uyandırıcı versiyonu [33:35] sunulurken, korumacı ve düşmanca cinsiyetçiliğin uyarıldığı gruplara ise aynı ayetlerin [4:34] farklı versiyonları sunulmuştur. Çelişkili cinsiyetçilik puanlarının uyarıcılara paralel olarak manipüle edilmesi beklenen çalışmada, ebeveyn dindarlığı ve (anne ve baba), katılımcıların dindarlığı ve kutsal kitapların değişmezliği, kontrol değişkenler olarak analize dâhil edilmiştir. Bulgular, kontrol grubu için sunulan mealin etkinliğini ortaya koymuştur. Buna ek olarak, erkekler tüm koşullarda kadınlardan daha yüksek puanlar elde etmiştir, ayrıca erkekler için düşmanca cinsiyetçilik başarılı bir şekilde uyarılmıştır, ancak kadınlar için cinsiyetçilik türlerinin hiçbiri başarılı bir şekilde uyarılamamıştır. Bu çalışmada, konuyla ilgili olan literatür ışığında, kontrol değişkenlerine dair ilave tartışmalar yapılmıştır. Anahtar Kelimeler: Çelişkili cinsiyetçilik, İslam, Dindarlık, Kur'ânî yorum,
Master of Science in General Psychology. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Psychology, 2020. Co-Supervisor: Assist. Dr. Deniz Atalar, Supervisor: Prof. Dr. Hüsnü Raman.
Keywords: Psychology; General Psychology; Sex (Psychology); Ambivalent sexism; Islam; Religiosity; Qur’anic interpretation